MANAGING DIGITAL TRANSFORMATION IN ISLAMIC BOARDING SCHOOL: LEADERSHIP STRATEGIES FOR E-LEARNING IMPLEMENTATION - Shaimaa Abdelmonem Ahmed; Ahmad Muchlis; Delta Yaumin Nahri; Hilmi Qosim Mubah (re-JIEM (Research Journal of Islamic Education Management), 2026)
Digital transformation has become a strategic priority for educational institutions seeking to improve learning quality, organizational effectiveness, and sustainable governance, including Islamic boarding schools with distinctive educational traditions and religious values. This study examined leadership strategies for managing digital transformation through the implementation of e-learning at Islamic Boarding School Padepokan Kyai Mudrikah Kembang Kuning in Pamekasan, Indonesia. A qualitative case study design was employed. Data were collected through semi-structured interviews, observations, and document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that successful digital transformation depends not merely on technology adoption but on leadership's capacity to integrate strategic leadership, resource management, human capacity development, and institutional adaptation into a sustainable organizational change process. The study contributes to the educational management literature by conceptualizing digital transformation as an organizational development process supported by institutional learning, collaborative governance, and adaptive management while preserving the educational identity and Islamic values that shape the long-term sustainability of e-learning implementation.